Integrating Maqashid al-Shari’ah into Sustainable Education: An Islamic Perspective on Global Citizenship Education - Salma Begum; Maryam Rashid Saleh Al Tamimi; Muneera Mohammed Al Dossary; Abdallah El-Khatib; Ainul Jaria Maidin (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
This study examines the integration of Maqāṣid al-Sharī‘ah into sustainable education as an Islamic framework for Global Citizenship Education (GCED). The research aims to explore the conceptual relationship between the higher objectives of Islamic law, sustainable education, and global citizenship competencies while identifying their potential contributions to contemporary educational challenges. Employing a qualitative library research design, the study utilizes a systematic literature review of scholarly publications, academic books, policy documents, and international reports. Data were analyzed using thematic content analysis to identify recurring concepts, theoretical convergences, and emerging educational trends. The findings reveal substantial alignment between Maqāṣid principles and the objectives of sustainable education, particularly in relation to human dignity, justice, public welfare, environmental stewardship, intellectual development, intercultural understanding, and social responsibility. The study further demonstrates that Maqāṣid-oriented education offers a holistic approach to learner development by integrating ethical, intellectual, spiritual, social, and ecological dimensions. The novelty of this research lies in the development of the Maqāṣid-Based Global Citizenship Education Framework (MB-GCEF), which synthesizes Islamic educational philosophy, sustainability education, and Global Citizenship Education into a comprehensive conceptual model. The framework provides a culturally inclusive and ethically grounded foundation for preparing learners to address contemporary global challenges while remaining committed to Islamic values. The study concludes that Maqāṣid al-Sharī‘ah can serve as a transformative educational paradigm capable of supporting sustainable development and responsible global citizenship in diverse educational contexts.